Business tourism in the function of improving the tourism in the city of Opatija - Romina Alkier Radnić; Ivan Herak; Andreja Rudančić-Lugarić (Ekonomski Vjesnik, 2013)
Tourism is an industry that transforms rapidly in the spheres of supply and demand. This has a strong influ - ence on the intensity and quality of tourism development in many Croatian destinations. A range of tourism forms have developed based on the changes in lifestyles, as well as in the way business activities are performed and organized. In this context, business tourism has taken an important place, with many indicators showing its expansion. Business tourism can help a destination to achieve various goals, such as urban reconstruction, improvement of infrastructure and increased tourist capacities. Big international conferences are a source of economic prosperity, but also of the destination’s international re - putation. This paper aims to gather and analyze quantitative and qualitative indicators of business tourism of the city of Opatija, and present applicative indicators through the share of business tourists in the overall number of visitors to Opatija. The paper will emphasize the crucial role of business tourism in the efforts to further improve an established tourist destination. Another purpose is to draw certain conclusions and offer subjective opinions that might help stakeholders to gain insights into both encouraging and warning aspects of this issue.